Any time you have an abs(something), write out the definition, as in:
abs(x - 3) = { x-3 when (x-3)>=0, and -(x-3) when (x-3)<0.}
Now use it in your expression:
abs(x - 3)
----------- =
(x - 3)
{ x-3 when (x-3)>=0, and -(x-3) when (x-3)<0}
--------------------------------------------------------- =
(x - 3)
Now x -->3- means x -> 3 from the left, therefore x < 3, therefore x - 3 < 0.
So { x-3 when (x-3)>=0, and -(x-3) when (x-3)<0} simplifies to -(x - 3) and your expression becomes:
-(x - 3)
---------- = - 1 and lim - 1 = -1.
(x - 3)
No worrying about small numbers,etc. Just very strict application of the def.